Sasandu Gong and Sasando Violin: Changing the Pentatonic Scales to Diatonic - Jefri Soli Kabnani (Institut Seni Indonesia Yogyakarta, 2021)
This study aims to determine the main causes of changes in the scales that occur. Changes in the scale of the Sasando musical instrument are influenced by mass culture, popular culture and the development of the market industry which has led to the tendency of the people of NTT, especially the city of Kupang to lead to Western lifestyles as if starting to leave local traditions. Values, meanings and social functions of Sasandu Gong are diminished and will even disappear in future generations. The influence of colonialism is assumed to be the cause of the people of Kupang prefer something modern than local wisdom. Some articles, journals, books and even websites often talk about the implementation of local cultural values as a cultural heritage and traditional art which is the identity of the Indonesian people. The author uses the concept of Leela Gandhi and Edward Said in general to discuss efforts to undermine Western hegemony, in which the domination of Western powers over the Eastern world considers the East as weak and full of imagination. The qualitative method is used as an exploratory approach that relies on in-depth data analysis in the form of text obtained from the speakers. The research results are discussed in three (3) stages. First, from the Postcolonial perspective that the change occurred starting from the history of the entry of Christianity into East Nusa Tenggara (NTT) by the Dutch people. Second, musicologically, Sasando Violin experienced the development of scales with several variations made by Mr. Drs. Djony L. K. Theedens. Third, the physicality of the sound of the Sasas Gong changes in shifting functions, values, and meanings that existed before.